Pharmaceutical Management Education and Development of Young Pharmapreneurs: Edukasi Manajemen Farmasi dan Pengembangan Jiwa Pharmapreneurs pada Generasi Muda - Rosa Mardiana; Nova Diansari; Nanda Silvia; Nova Fahlevi (Akademi Farmasi YPPM Mandiri, 2026)
The pharmaceutical management education and pharmapreneurs development program was conducted at SMA Negeri 12 Banda Aceh, attended by 60 senior high school students (Grade XII). The program included sessions on pharmaceutical management theory, hands-on production of simple pharmaceutical products, business model canvas simulation, and group business plan presentations. Experiential learning, gamification, and group collaboration approaches were applied to enhance conceptual understanding, managerial skills, creativity, leadership, and entrepreneurial motivation. Evaluation results showed significant improvements in pharmaceutical management knowledge, decision-making skills, innovation capability, and business ethics awareness. The program stands out for integrating theory, practice, simulation, and social ethics holistically, preparing participants to become competent, creative, and socially responsible pharmapreneurs. Activity documentation supports the evidence of active participation and the effectiveness of the interactive learning approach.